2014
DOI: 10.3322/caac.21235
|View full text |Cite
|
Sign up to set email alerts
|

Cancer treatment and survivorship statistics, 2014

Abstract: The number of cancer survivors continues to increase due to the aging and growth of the population and improvements in early detection and treatment. In order for the public health community to better serve these survivors, the American Cancer Society and the National Cancer Institute collaborated to estimate the number of current and future cancer survivors using data from the Surveillance, Epidemiology, and End Results (SEER) program registries. In addition, current treatment patterns for the most common can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
1,950
0
38

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,583 publications
(2,063 citation statements)
references
References 94 publications
16
1,950
0
38
Order By: Relevance
“…41,42 In addition, melanomas are exceptionally resistant to chemotherapy treatment and have a high incidence of relapse. [43][44][45][46][47] Our previous 8 and current studies have revealed a prominent role of deregulated guanylate pools in melanoma progression. Altered expression of enzymes involved in guanylates biosynthesis priming the cells toward an increase in guanylates production occurs already in primary melanomas (GMPR) and peaks at the metastatic stage (IMPDH2, GMPR, and GMPS) (Wawrzyniak et al 8 and Figure 3 and Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 57%
“…41,42 In addition, melanomas are exceptionally resistant to chemotherapy treatment and have a high incidence of relapse. [43][44][45][46][47] Our previous 8 and current studies have revealed a prominent role of deregulated guanylate pools in melanoma progression. Altered expression of enzymes involved in guanylates biosynthesis priming the cells toward an increase in guanylates production occurs already in primary melanomas (GMPR) and peaks at the metastatic stage (IMPDH2, GMPR, and GMPS) (Wawrzyniak et al 8 and Figure 3 and Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 57%
“…Surgical resection of a tumor is the preferred option, especially at early stages of disease 3. However, surgery is often not possible for several reasons, including the type, location, stage of cancer, and underlying diseases.…”
Section: Introductionmentioning
confidence: 99%
“…2 Dentre as formas de tratamento das neoplasias, a quimioterapia é a mais frequente, e até 70% dos tumores necessitarão de tratamento quimioterápico em algum momento do curso da doença. 3 A avaliação da qualidade de vida (QV) de pacientes em tratamento quimioterápico possibilita melhor compreensão da intensidade e quantidade dos sintomas do paciente e da importância que isso tem na sua saúde, permitindo também melhorar o planejamento da estratégia terapêutica. 3 A QV é uma noção eminentemente humana, que tem sido correlacionada ao grau de satisfação encontrado na vida familiar, amorosa, social e ambiental, e à própria estética existencial.…”
Section: Introductionunclassified
“…3 A avaliação da qualidade de vida (QV) de pacientes em tratamento quimioterápico possibilita melhor compreensão da intensidade e quantidade dos sintomas do paciente e da importância que isso tem na sua saúde, permitindo também melhorar o planejamento da estratégia terapêutica. 3 A QV é uma noção eminentemente humana, que tem sido correlacionada ao grau de satisfação encontrado na vida familiar, amorosa, social e ambiental, e à própria estética existencial. 4 Na área de saúde, o conceito mais utilizado tem sido o de "qualidade de vida relacionada à saúde" (QVRS) que carece de definição única.…”
Section: Introductionunclassified